2003
DOI: 10.3748/wjg.v9.i11.2570
|View full text |Cite
|
Sign up to set email alerts
|

Organ failure associated with severe acute pancreatitis

Abstract: AIM: To investigate the relationship between severe acute pancreatitis (SAP) and organ failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…However, the underlying mechanisms of ARI occurring in patients with SAP have remained to be clarified. Increasing evidence has indicated that pro-inflammatory cytokines, including tumor necrosis factor-α (TNF-α) and interleukin (IL)-6, have an important role in the pathological mechanisms of SAP and SAP-associated organ failure (2)(3)(4). Therefore, inhibiting the transcription and translation of mediators to reduce the secretion of pro-inflammatory factors may ameliorate inflammation and renal failure in SAP.…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying mechanisms of ARI occurring in patients with SAP have remained to be clarified. Increasing evidence has indicated that pro-inflammatory cytokines, including tumor necrosis factor-α (TNF-α) and interleukin (IL)-6, have an important role in the pathological mechanisms of SAP and SAP-associated organ failure (2)(3)(4). Therefore, inhibiting the transcription and translation of mediators to reduce the secretion of pro-inflammatory factors may ameliorate inflammation and renal failure in SAP.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is certainly related to two major reasons: the retrospective research has limits in our included studies, and the population is linked to the homogeneity in the study. Several studies have proposed organ failure as a significant factor to stratify the severity of disease, and it was closely associated with mortality in infected pancreatic necrosis [30,[38][39][40][41]. In this systematic review, 53.6 % of patients had organ failure, with nine reported single and multisystem organ failures (MSOF) in our study.…”
Section: Discussionmentioning
confidence: 84%
“…Among the single-organ failures in AP, pulmonary failure is the most common in cases of severe AP [16]. Our patient had respiratory distress 24 hours after presentation, and she required intubation and mechanical ventilation for the next 4 days.…”
Section: Discussionmentioning
confidence: 99%